2022
DOI: 10.1177/09603271221136205
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of ferulic acid and/or low doses of γ-irradiation against cisplatin-induced liver injury in rats

Abstract: The therapeutic efficacy of cisplatin (CIS) is limited owing to its hepatotoxic side effects. The current study aimed to investigate the protective impact of ferulic acid (FA) and low-doses of γ-irradiation (LDR) against CIS-prompted hepatotoxicity in rats. Adult male Swiss albino rats were divided into eight groups: untreated group; FA, LDR, and CIS treated groups; and combinations of one or more of the above treatments. Post-treatment analyses included measuring redox markers like SOD and CAT activity, NO fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…[58][59][60][61][62] Results of various non-clinical and preclinical tests demonstrated that FA and its different derivatives have remarkable antioxidant activity as the chemicals increase the activity of antioxidant enzymes and reduce oxidative stress. [63,64] In a study by (Esmat et al, 2022), it was stated that FA at the dose of 40 mg/kg significantly reduced oxidative stress with enhancing the activity of antioxidants such as SOD and CAT in the cisplatin-induced injured liver of rats. [63] Another study by (Ahmadipour et al, 2021) also reported that FA at doses of 10 and 20 mg/kg remarkably reduced oxidative stress in isoniazid- Review induced hepatotoxic rats by reducing the oxidative stressrelated marker MDA and increasing the level of antioxidant enzymes (e. g. SOD, CAT, and GPx).…”
Section: Inhibition Of Oxidative Stress and Ros Generationmentioning
confidence: 99%
See 3 more Smart Citations
“…[58][59][60][61][62] Results of various non-clinical and preclinical tests demonstrated that FA and its different derivatives have remarkable antioxidant activity as the chemicals increase the activity of antioxidant enzymes and reduce oxidative stress. [63,64] In a study by (Esmat et al, 2022), it was stated that FA at the dose of 40 mg/kg significantly reduced oxidative stress with enhancing the activity of antioxidants such as SOD and CAT in the cisplatin-induced injured liver of rats. [63] Another study by (Ahmadipour et al, 2021) also reported that FA at doses of 10 and 20 mg/kg remarkably reduced oxidative stress in isoniazid- Review induced hepatotoxic rats by reducing the oxidative stressrelated marker MDA and increasing the level of antioxidant enzymes (e. g. SOD, CAT, and GPx).…”
Section: Inhibition Of Oxidative Stress and Ros Generationmentioning
confidence: 99%
“…[63,64] In a study by (Esmat et al, 2022), it was stated that FA at the dose of 40 mg/kg significantly reduced oxidative stress with enhancing the activity of antioxidants such as SOD and CAT in the cisplatin-induced injured liver of rats. [63] Another study by (Ahmadipour et al, 2021) also reported that FA at doses of 10 and 20 mg/kg remarkably reduced oxidative stress in isoniazid- Review induced hepatotoxic rats by reducing the oxidative stressrelated marker MDA and increasing the level of antioxidant enzymes (e. g. SOD, CAT, and GPx). [65] FA (25-100 mg/kg) also reduced oxidative stress induced by methotrexate (20 mg/kg) by boosting the activity of antioxidant enzymes (e. g., GSH, CAT, SOD, and GPx), resulting in an improvement of hepatic damage.…”
Section: Inhibition Of Oxidative Stress and Ros Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Carvacrol monocyclic monoterpene alcohol 🌱✿ [49] antibacterial (64); antifungal [63]; antioxidant [64]; anticancer [65]; anti-inflammatory, analgesic [66]; antiobesity [67]; hepatoprotective [68]; spasmolytic [69]; vasorelaxant [70]; 7 β-Cyclocitral oxygenated monocyclic monoterpene 🌱 [53] n/a [12] antioxidant [199]; antimicrobial [200]; anti-inflammatory [201]; neuroprotective [202]; antiviral [203]; antiallergic [204]; hepatoprotective [205]; anticancer [206]; antithrombotic [207]; antidiabetic [208];…”
Section: Nomentioning
confidence: 99%